Антология выдающихся достижений в науке и технике. Часть 43: Традиционная энергетика. Тепловые электрические станции: состояние и перспективы их развития - Баранов, М.И. (Електротехніка і електромеханіка, 2018)
Приведен краткий научно-аналитический обзор о современном техническом состоянии и ближайших перспективах развития мировой теплоэнергетики. Рассмотрены основные теплоэнергоустройства, схемы построения и виды тепловых электрических станций (ТЭС). Указаны преимущества и недостатки ТЭС перед другими видами электрических станций, генерирующих тепло и электричество. Приведены основные технические характеристики крупнейших ТЭС Украины. Обозначены существующие проблемные задачи и возможные пути их решения в области теплоэнергетики Украины Наведено короткий науково-аналітичний огляд про сучасний технічний стан і найближчі перспективи розвитку світової теплоенергетики. Розглянуті основні теплоенергопристрої, схеми побудови і види теплових електричних станцій (ТЕС). Вказані переваги і недоліки ТЕС перед іншими видами електричних станцій, що генерують тепло і електрику. Приведені основні технічні характеристики найбільших ТЕС України. Позначені існуючі проблемні завдання і можливі шляхи їх рішення в галузі теплоенергетики України. Purpose. Preparation of brief scientific and technical review with an analytical analysis about the state, achievements, problems and prospects of development of world thermal power engineering. Methodology. Known scientific methods of collection, analysis and analytical treatment of the opened scientific and technical information, present in scientific monographs, journals and internet reports, world level in area of thermal power engineering. Results. A brief analytical scientific and technical review is resulted about the present state, achievements, problem tasks and prospects of development of thermal power engineering in the industrially developed countries of the world. Considerable progress is marked in development and creation of technical base of modern thermal power engineering including such thermal power devices (TPD) as steam generators, steam turbines and turbogenerators. Basic TPDs are described, charts of design and types of the modern thermal power plants (TPP), producing in the world about 70 % annual production electric power are presented. From positions of approach of the systems advantages and lacks of TPPs are described before other types of electric stations, generating heat and electric energy in industrial scales. Basic technical descriptions of largest TPPs of Ukraine are resulted, TPDs of powerful power units of which behave to the morally out-of-date past generation and characterized a large physical wear. Some topical problem tasks and possible ways of their decision are indicated in area of thermal power engineering of Ukraine. In a review an accent is done on the necessity of development and acceptance of strategic plan of development of thermal power engineering of Ukraine on the nearest 10 years. A regard is paid to power engineering experts acceleration of rates of introduction in domestic practice of achievements alternative and ecologically clean power engineering specialists − especially wind energy and sun energy. Originality. Systematization of the scientific and technical materials touching functioning of such important sector of world economy as thermal power engineering known from the sources opened in outer informative space is executed. It is shown that for normal development and determination of the nearest prospects for domestic thermal energy the native revision of power politics of Ukraine is needed. Practical value. Popularization and deepening for students, engineers and technical specialists and research workers of front-rank scientific and technical knowledge in area of modern thermal energy, extending their scientific range of interests and further development of scientific and technical progress in society.